Model Collaborative Governance dalam Penyediaan Perumahan (Studi pada Program Rehabilitasi Sosial Rumah Tak Layak Huni di Kota Prabumulih Provinsi Sumatera Selatan) - Priadi, Aris; Sobri, M.; Setyoko, Paulus Israwan; Putra, Raniasa (Jayapangus Press, 2024)
This research aims to explore the concepts and theories of collaborative governance models in addressing the social rehabilitation program for uninhabitable houses in the region. The benefits involve offering recommendations to the government regarding responsive local government models in addressing uninhabitable houses, providing policy suggestions for involving the community in handling such situations, contributing to the development of Public Administration knowledge, and creating effective public policies in dealing with uninhabitable houses. The research utilizes a qualitative method with a descriptive approach. Results indicate significant participation involving various stakeholders such as government, private sector, and the community. The acceleration of uninhabitable house rehabilitation in Prabumulih City has positive impacts on the economy and health. The research concludes that a collaborative governance-based social rehabilitation program management, with facilitative leadership and institutional design supporting private sector and community participation, can achieve optimal results in addressing uninhabitable houses.